2004
DOI: 10.1001/archpsyc.61.7.658
|View full text |Cite
|
Sign up to set email alerts
|

Pathways That Make Voices

Abstract: Our findings suggest that during inner speech, the alterations of white matter fiber tracts in patients with frequent hallucinations lead to abnormal coactivation in regions related to the acoustical processing of external stimuli. This abnormal activation may account for the patients' inability to distinguish self-generated thoughts from external stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 438 publications
(139 citation statements)
references
References 60 publications
10
127
1
1
Order By: Relevance
“…This study also reported that the visual cortex of hallucinators was less responsive to external stimulation, which we also found in the lower N1 VEP of the VH subgroup. Still another possibility is that the correlations between increased phase locking and symptoms ref lects the presence of abnormally increased connectivity in particular neural circuits, as was recently reported for SZ with auditory hallucinations (36).…”
Section: Discussionmentioning
confidence: 69%
“…This study also reported that the visual cortex of hallucinators was less responsive to external stimulation, which we also found in the lower N1 VEP of the VH subgroup. Still another possibility is that the correlations between increased phase locking and symptoms ref lects the presence of abnormally increased connectivity in particular neural circuits, as was recently reported for SZ with auditory hallucinations (36).…”
Section: Discussionmentioning
confidence: 69%
“…AVHs, on the other hand, were attributed to the sensory functions of the language system, since they consist in an abnormal perception of speech [9, 49-51]. …”
Section: Translational Psychopathology: Matching Psychotic Symptoms Wmentioning
confidence: 99%
“…A later diffusion tensor imaging study suggested an increased connectivity within the left arcuate fascicle, which is a major intrahemispheric fiber tract connecting frontal to temporal components of the language system. This finding was specific for schizophrenia patients with frequent hallucinations compared to schizophrenia patients who had never hallucinated as well as healthy controls [49]. Furthermore, it was demonstrated that the effect of phasic activation of Heschl’s gyrus during hallucinations could not be explained by external stimulation, but rather by sequestration of temporal lobe resources by internal processes [88].…”
Section: Mapping Symptoms Onto Brain Systems: Empirical Evidence For mentioning
confidence: 99%
“…Notwithstanding the overall reduced FA, a higher FA in WM tracts connecting the temporal regions has been consistently associated with worse hallucinations [31]. The involved tracts included the arcuate fasciculus [32,33] and the corpus callosum, superior longitudinal fasciculus and the cingulum bundle [32,34,35]. A higher FA was also observed in dopaminergic tracts in the mesencephalon of drug-naive schizophrenics and of their unaffected relatives [30].…”
Section: Discussionmentioning
confidence: 99%